Comparative Study on the Test Method for Tensile Elastic Modulus of Rock Materials. (1st July 2019) - Zhang, Yan; Yu, Dawei
Abstract : Rock material has different mechanical behaviors under compressive and tensile loading. Correspondingly, there are two types of elastic modulus: compressive elastic modulus E c and tensile elastic modulus E t, respectively. To distinguish which indirect test methodology, including three-points bending test and Brazilian disc test, is more suitable to measure the tensile elastic modulus E t of rock materials, a series of uniaxial compressive test (UCT), direct tensile test (DTT), three-points bending test, and Brazilian disc test are performed for three typical types of rock: marble, granite, and sandstone. Comparative investigation on the reliability of measurement results of tensile elastic modulus E t is systematically conducted. Finally, it is found that Brazilian disc test could be a suitable method to measure tensile elastic modulus of rock materials, due to the excellent agreement with that measured by DTT and the simplicity of sample preparation, as well as test operation.